(untitled) (Medical Forum Monthly, 2020)
Objective: To study the outcome of corticosteroids injections in De Quervain’s disease produces lateral wrist pain and can also cause acute conditions subsequently leading to disabilities .In this condition pain is caused by thumb movement and radial and ulnar deviance of the wrist. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the Islam Medical College of Sialkot from January 2018 to January 2019. Materials and Methods: All patients with De Quervain’s disease are included in our study. This study includes 152 patient. We recorded the tenderness on first dorsal compartment and pain felt on Finkelstein test using Visual analogue scale before and after the treatment fortnightly and within 30 days. We also noted the Mean Age gender wise and recorded treatment results for statistical analysis using SPSS Version-20. Results: In our data De Quervain’s disease was found in 60 males (33% of total patients) and 92 females (67% of total patients) with a male to female ratio of 1:1.5 .The Mean age group recorded was 36.80 ± 4.462 years and a mean Vas score (mm) of 93.9 before injection and 6.38 post-injection was observed with a mean success rate of 89% and significant improvement in pain on the radial side of wrist and we observed a negative Finkelstein test post-injection. Conclusion: Thus we find that steroid injections assist in significant improvement in De Quervain’s disease and helps in reducing re-occurrence.